THE INFLUENCE OF USEFUL, EASE, TRUST, AND CONVENIENCE INTEREST IN CUSTOMER BEHAVIOR AND DECISION USING INTERNET BANKING IN THE UNIT OF PT. BANK RAKYAT INDONESIA TBK. BRANCH AHMAD YANI MAKASSAR - Andi Tenri Nur Fatimah; Dian AS Parawansa; Abdul Razak Munir (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2020)
The banking world is a business that greatly influences the economic base, with the condition of increasing internet users from year to year, the business world, including the banking sector, also utilizes internet media in conducting business activities. The research that will be conducted at this time focuses on the use of Internet Banking for BRI Butung Unit customers. The process of distributing questionnaires takes 2 weeks. The method of data collection uses the method of data collection through the distribution of questionnaires to respondents. In this study the independent variables (exogenous) are usability (X1), Ease (X2), trust (X3), and Convenience (X4) while the dependent variable (endogenous) studied is interest in using (Y1) and decided to use (Y2). The results of the study indicate that there is an influence of usability on interest in using internet banking. The higher the perception of the usefulness of customers, the higher the interest in using Internet banking because customers believe that the use of Internet banking can have a positive influence and can improve business transactions. The results of the study indicate that there is no effect of ease on interest in using internet banking. It is expected to always update the internet banking system used, both in terms of the type of transaction and the appearance of the system and innovate new facilities so that it can provide direct benefits, reduce the level of difficulty and complexity of transactions and simplify the operation of the system so that customers can more easily transact using Internet banking.